PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PESERTA DIDIK KELAS XI MIA SMA NEGERI 3 PADANG - Rambe, Hotmana Rezki (journal of residu, 2019)
Problem solving skilss are one of the purpose of mathematical learning expected by learners in the learnig process of mathematical learning. But th real problem solving, the learners are still not very good. It is seen from observation that learners are not familiar with problem solvinng. As for the daily exams 2018/2019 result which show the students grades have not yet been completed. Efforts to overcome the poor ablility to solve problems of maths learners, researchers use learning models type think talk write is better than the ability to solve problems for learners with convensional learnig models.The types of this research was quasi-experimental with the design of Randomized Control-Group Only design. The subject of this student is mia’s class protege,hight school in the country of 3 Padang composed og eight classes, the student used 11th  grade mia one as experiment class and 11th grade mia second as control class. Reseacrh tests based on the t test suggest that the cooperative learning model of the think talk write type has an influence on abilities solving problems for math using convensional learning models,the point that five percent of errors were made score P-Value is  0,076 for experiment class whereas the firts class controls score P-Value is 0,080